(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This article considers the issues of phraseological connotation in a literary text, phraseology issues from the perspective of cultural linguistics, different approaches to phraseological units classification in contemporary linguistic studies, functional-stylistic and emotional-expressive features of phraseological units in a literary text. By phraseological unit we mean fixed combinations of words characterized by constant lexical composition, grammatical structure and meaning that is known to the language speakers and that is not derived from the meaning of the constituent components.